Central and Eastern Europe : roads to growth: papers presented at a seminar held in Baden, Austria, April 15-18, 1991 (International Monetary Fund ; Austrian National Bank, 1992)
The experience of Central and Eastern European countries with moving from centrally planned to open-market economies is examined in this collection of papers given at an April 1991 seminar, moderated by Georg Winckler and organized by the IMF and the Austrian National Bank.
Keywords: Europe, Central -- Economic policy -- Congresses.; Europe, Eastern -- Economic policy -- 1989- -- Congresses.; Europe, Eastern -- Economic policy -- Congresses.; Europe centrale -- Politique économique -- Congrès.; Europe de l'Est -- Politique économique -- Congrès.; Europe de l'Est -- Politique économique -- 1989- -- Congrès.; BUSINESS & ECONOMICS -- Economic Conditions.; BUSINESS & ECONOMICS -- Economic History.; BUSINESS & ECONOMICS -- Economics -- Comparative.; POLITICAL SCIENCE -- Economic Conditions.; Economic policy; Central Europe; Eastern Europe; Wirtschaftspolitik; Kongress; Wirtschaftsreform; Osteuropa; Economische politiek.; Wirtschaftspolitik.; Mitteleuropa.; Osteuropa.; Since 1989; Osteuropa -- Wirtschaftspolitik -- Kongress -- Baden (Niederösterreich, 1991); Osteuropa -- Wirtschaftsreform -- Kongress -- Baden (Niederösterreich, 1991); Conference papers and proceedings